SGCE Myoclonus-Dystonia: An Inherited Movement Disorder. (15th February 2022) - Yoganathan, Sangeetha; Kumar, Madhan; Sharma, Suvasini; Patel, Smruti; Danda, Sumita; Thomas, Maya
Abstract : A 5-year-old girl presented with myoclonus and frequent falls for 2.5 years. Myoclonus involving arms and axial muscles with dystonia of left foot (Video) was observed. Her paternal grandmother and father had a similar phenotype of varying age at onset and severity. Possibilities of SGCE myoclonus-dystonia, ADCY5 -related dyskinesia, dentatorubral-pallidoluysian atrophy, and myoclonic dystonia 26 were considered. A pathogenic heterozygous nonsense variant (c.304C>T; p.Arg102Ter) in exon 3 of the epsilon-sarcoglycan ( SGCE ) gene was identified.